Methodology for the analysis and design of radiant elements such as microstrips - Herrera Rubio, Jorge Enrique (2025)
Microstrip antennas were researched and developed in the 1970s. With advances in microelectronics, they have gained significant relevance in new emerging technologies, such as mobile phones, Bluetooth radio devices, IoT, and Wi-Fi. They are used in applications such as satellite communications, radio communications, telemetry, mobile communications, and radar systems.They are constructed of a plate of conductive material that can be rectangular, circular, or elliptical, placed on a dielectric substrate and a ground plane on the other side of the dielectric with a conductive material such as copper. These antennas are fed through a coaxial conductor or a microstrip line. The impedance matching of the antenna and the feed line to the radiating plate can be affected depending on the feed point, which can generate changes in the antenna’s radiation.The research delves into the design, analysis, and construction condensed into four chapters: the first uses theoretical references; the second delves into the fundamentals of the electric dipole; the third details the structure and components; and finally, the design methodology and parameters are established with a practical approach.
Keywords: Microstrips; Conductive material; Dielectric; Radiant element; Design